Social Media Advertising: How Do Consumers Respond to Ads on Instagram? - Rabbani, Maheswara; Burhan, Angelina Gracia Eddyputri (AI Society & STMIK Indonesia, 2023)
Utilization of social media marketing greatly influences a brand in terms of awareness, the relationship between the organization and consumers, and purchase intention. Therefore this research was conducted to study the interactions that social media users give to image or video advertisements displayed on Instagram. The research model used in this study is descriptive quantitative, by distributing questionnaires to respondents online via Google form. The study uses descriptive statistical analysis to measure the average, frequency distribution, and calculate the value of the distribution in the resulting data. The results of this study indicate that there is an influence on consumer response to advertisements on social media Instagram. This study shows that Instagram is the right choice for one of its marketing strategies because consumers give a good response.